Die Entwicklung des Lebensstandards im Dritten Reich : eine glücksökonomische Perspektive - Wahl, Fabian (FZID discussion papers, 2011)
The goal of this paper is to provide an explanation for the remarkable difference in the contemporary Germans positive self-assessment of their living conditions and the development of the most important economic welfare indicators (like GDP or consumption per capita) during the Third Reich. To explain this discrepancy, findings of the new research field of happiness economics are applied to the peacetime of the Third Reich to analyze the development of the standard of living in this period. First, the theory of adaption and aspiration is used to explain the growing satisfaction of the Germans after the Great Depression. In the second step, based on current life satisfaction studies, the development of the most important economic determinants of happiness during the 1930s is examined. -- Economic History ; Third Reich ; Happiness Economics ; Standard of Living